Racism, culture, markets - Gabriel, John, 1951- (Routledge, 1994)
With the aid of case studies, which include the Bhopal disaster and the Rushdie Affair, John Gabriel explores the connections betweeen cultural representations of r̀ace' and their historical, institutional and global forms of expression.